Super fly guy! eaudiobook - Arnold, Tedd (Fly Guy, 2017)
Tedd Arnold's hilarious SUPER FLY GUY, originally published in 2006, is now available in paperback with foil on the cover! The second book in a humorous, award-winning series about a boy and his pet fly is now available as a Level 2 reader!Fly Guy loves the school lunchroom. But when the lunch ladies discover there's a fly in the cafeteria, chaos ensues!Using hyperbole, puns, slapstick, and silly drawings, bestselling author/illustrator Tedd Arnold creates an easy-to-read story that is full of fun and excitement.